Effectiveness of Ball Attachment Systems in Implant Retained- and Supported-Overdentures: A Three- to Five-Year Retrospective Examination - Luca Ortensi; Matteo Martinolli; Carlo Borromeo; Francesco Mattia Ceruso; Marco Gargari; Erta Xhanari; Marco Tallarico (MDPI AG, 2019)
Purpose: To evaluate implant and prosthetic survival rates, complications, patient satisfaction, and biological outcomes of patients rehabilitated with a ball attachment system for implant retained- and supported-overdentures (IOV), which was in function for 3 to 5 years. Methods: This retrospective study evaluated data collected from patients treated between April 2001 and May 2018 with IOV on splinted and non-splinted implants and a ball attachment system. Patients were followed for 36 to 206 months (mean follow-up was 128.1 ± 51.9 months). Data were collected at the 3- and 5-year follow-up examination. Outcome measures were implant and prosthetic survival rates, technical complications, marginal bone loss (MBL), oral health impact profile (OHIP), and periodontal parameters (bleeding on probing and plaque index). Results: A total of 46 patients (16 males and 30 females) with 124 implants were included in this study. Twenty-five implant-retained overdentures were delivered on 53 unsplinted implants, while the other 21 patients received an implant-supported overdentures and the implants were splinted. At the five-year follow-up examination, one implant and one prosthesis failed in the unsplinted group, resulting in a cumulative survival rate of 97.8% at the patient level. Two minor technical complications were experienced. Conclusions: Implant overdenture retained or supported by ball attachment systems showed high implant and prosthetic survival and success rates. A low number of complications, high patient satisfaction, and successful biological parameters were experienced in the mid-term follow-up. Data need to be confirmed by further randomized trials.